2021
DOI: 10.18178/ijiet.2021.11.9.1543
|View full text |Cite
|
Sign up to set email alerts
|

Involving Students in the Instructional Design Process to Improve Their Satisfaction with Their Learning in the COVID-19 Era

Abstract: Like most university students worldwide, the engineering students at the School of Information Sciences (ESI) have to deal with their school closure and the new paradigm of distance learning. Despite efforts made by the administration and the teachers to accompany students, an internal survey conducted by the end of October 2021 revealed that almost all students, especially first-year ones, did not accept distance learning. This paper describes our experience to improve students’ satisfaction with distance lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Instructional design: It is a process that takes learning objectives as input and leads to the modeling of the learning system in terms of activities and learning content [15]. Instructional design refers to a series of systematic processes that translate principles of learning and teaching into practical plans for the development of instructional materials, activities, information sources, and assessment [16].…”
Section: Study Termsmentioning
confidence: 99%
“…Instructional design: It is a process that takes learning objectives as input and leads to the modeling of the learning system in terms of activities and learning content [15]. Instructional design refers to a series of systematic processes that translate principles of learning and teaching into practical plans for the development of instructional materials, activities, information sources, and assessment [16].…”
Section: Study Termsmentioning
confidence: 99%
“…An investigation of the MOOC composition was conducted by performing several studies, as shown in Table 2 [22][23][24][25][26][27][28][29]:…”
mentioning
confidence: 99%